Pengembangan Miniatur Konversi Energi Gerak Sebagai Media Pembelajaran Fisika Kontekstual - Nuril Husna; Muhammad Yakob; Dona Mustika (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2019)
This study aims to determine the miniature of the conversion of motion energy can be used as a medium for contextual physics learning. This type of research is development research using the R & D (Research and Development) method which adopts the development of Gravermaijer and Cobb. The population in this study were all class X in SMA Negeri 4 Langsa and the sample in this study was class X MIPA 1 with a total of 22 students. The results of this study are miniatures of the conversion of motion energy into electrical energy. The value of media validation gained 99% and material validation was 82.5%. Based on the validation values, the developed media is declared suitable for use as a contextual physics learning media for energy conversion material. The results of student responses also showed that learning physics using miniature energy conversion was